P-TEFb: Finding its ways to release promoter-proximally paused RNA polymerase II. Issue 2 (15th March 2018) - Li, You; Liu, Min; Chen, Lin-Feng; Chen, Ruichuan
ABSTRACT: The release of a paused Pol II depends on the recruitment of P-TEFb. Recent studies showed that both active P-TEFb and inactive P-TEFb (7SK snRNP) can be recruited to the promoter regions of global genes by different mechanisms. Here, we summarize the recent advances on these distinct recruitment mechanisms.